2014
DOI: 10.1074/mcp.m114.039156
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptomic and Proteomic Analysis of the Bile Stress Response in a Centenarian-originated Probiotic Bifidobacterium longum BBMN68

Abstract: Bifidobacteria are natural inhabitants of the human gastrointestinal tract and well known for their health-promoting effects. Tolerance to bile stress is crucial for bifidobacteria to survive in the colon and to exert their beneficial actions. In this work, RNA-Seq transcriptomic analysis complemented with proteomic analysis was used to investigate the cellular response to bile in Bifidobacterium longum BBMN68. The transcript levels of 236 genes were significantly changed (> threefold, p < 0.001) and 44 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 105 publications
4
76
0
Order By: Relevance
“…Furthermore, the GroEL/ES complex is responsible for appropriate protein folding and frequently participates in response to diverse stresses. The transcription of groES is also increased with exposure to bile salts or acidic environments (Wu et al, 2012;An et al, 2014). Analogously, chaperone GroEL upregulation preserves protein function under acid stress in Strep.…”
Section: Effects Of Cross-stress On General Stress Response and Dna Rmentioning
confidence: 99%
“…Furthermore, the GroEL/ES complex is responsible for appropriate protein folding and frequently participates in response to diverse stresses. The transcription of groES is also increased with exposure to bile salts or acidic environments (Wu et al, 2012;An et al, 2014). Analogously, chaperone GroEL upregulation preserves protein function under acid stress in Strep.…”
Section: Effects Of Cross-stress On General Stress Response and Dna Rmentioning
confidence: 99%
“…A binding site motif can be determined from the sequences obtained and then the bacterial genome can be scanned for the motif to identify target promoters (Meng et al ., ; Meng and Wolfe, ). The bacterial one‐hybrid screen has been successfully used to determine the regulon for a few RRs (Tomljenovic‐Berube et al ., ; An et al ., ; Svensson et al ., ; Hebdon et al ., ). This screen can also be used to determine the TFs that bind to a particular promoter of interest, as was done for M .…”
Section: Binding Site Mapping Techniquesmentioning
confidence: 98%
“…longum BBMN68 (CGMCC 2265) was isolated from healthy centenarians in Bama longevity villages of Guangxi province in China (Yang et al ., ). In previous work from our research group, RNA‐Seq transcriptomic analysis showed that the tlyC1 gene from B. longum BBMN68 was 10‐fold upregulated upon ox‐bile exposure (An et al ., ). TlyC1 is a hemolysin‐like protein (HLP), belonging to the large YGGT protein family (EMBL InterPro accession no.…”
Section: Introductionmentioning
confidence: 97%